The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21037/atm-21-5200
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an early predictive nomogram for delayed cerebral ischemia after aneurysmal subarachnoid hemorrhage

Abstract: Background: Previous studies have shown that platelet is involved in the occurrence and progression of delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (aSAH), but the relationship between platelet and DCI is not completely clear. Here, we aimed to screen the early platelet parameters associated with DCI after aSAH and develop an early predictive nomogram for DCI after aSAH. Methods:The study was carried out in the neurosurgery department of Affiliated Hospital of North Sichuan Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The occurrence of DCI after aSAH has been widely reported regarding age, hydrocephalus, modified Fisher grade (mFisher) and other biomarkers. For example, Plasma Galectin-3, c-reactive protein (CRP), mean platelet volume (MPV), coagulation abnormalities, electrolyte disturbances, and neutrophil/lymphocyte ratio (NLR) are all associated with DCI or poor prognosis of aSAH (4)(5)(6)(7)(8)(9). In the latest study, some scholars found that early cerebrospinal fluid lactic acid and glucose levels also have a certain predictive effect in the occurrence of symptomatic DCI (10).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of DCI after aSAH has been widely reported regarding age, hydrocephalus, modified Fisher grade (mFisher) and other biomarkers. For example, Plasma Galectin-3, c-reactive protein (CRP), mean platelet volume (MPV), coagulation abnormalities, electrolyte disturbances, and neutrophil/lymphocyte ratio (NLR) are all associated with DCI or poor prognosis of aSAH (4)(5)(6)(7)(8)(9). In the latest study, some scholars found that early cerebrospinal fluid lactic acid and glucose levels also have a certain predictive effect in the occurrence of symptomatic DCI (10).…”
Section: Introductionmentioning
confidence: 99%
“…RBC parameters including hemoglobin, RBC, hematocrit, MCV, MCH, mean corpuscular hemoglobin concentration (MCHC), and RDW were collected on admission and postoperatively. Other CBC parameters reported as outcome predictors were also collected, including white blood cell (WBC), neutrophil, lymphocyte, monocyte, platelet and mean platelet volume (MPV) (11)(12)(13). Differences between admission and postoperative RBC parameters were calculated by subtracting the admission values from the postoperative values.…”
Section: Data Collection and Definitionmentioning
confidence: 99%
“…A total of 187 patients were included in this study, of which 114 (61.0%) had good functional outcome while 73 (39.0%) had poor functional outcome, including 15 patients (8.0%) who died within 3 months of the onset (Figure 1). Of the included cases, 122 were included in a published article to establish an early predictive nomogram for DCI after aSAH (13). Parameters of demographics, addictions, medical history and aneurysm characteristics showed no significant differences between two groups.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…A mathematical model capable of predicting the risk of lower extremity DVT for RIA patients may be an approach to address this problem. A nomogram is a graphical depiction that presents a regression model in a friendly manner and simplifies risk assessment, providing medical staff with a user-friendly interface to map the probability of an event to individual patients, which has widely been used in intracranial aneurysms research (16)(17)(18). The purpose of this study is to develop and validate a nomogram model, thus providing a promising and facile avenue for predicting the risk of lower extremity DVT after RIA patients underwent EVT and promoting patient recovery.…”
Section: Introductionmentioning
confidence: 99%